1.
Find
g.c.d, l.c.m and x,y such that d= ax+by, d=(a,b) where
i)
a= 322
and b=770
Solution:
770 = 2´322+126
322 = 2´126+70
126 = 1´70+56
70 = 1´56+14
56 = 4´14+0
Hence g.c.d =d(770,322)=14
Again
dl=ab
14´l= 770´322
\ l = 17710.
Now for x and y
126= 770-2´322
70= 322-2´126
= 322-2´(770-2´322)
= 1´322-2´770+4´322
= 5´322-2´770
56= 126-1´70
= 770-2´322-1´(5´322-2´770)
= 770-2´322-5´322+2´770
= 3´770-7´322
14= 70-1´56
= 5´322-2´770-1´(3´770-7´322)
= 5´322-2´770-3´770+7´322
=-5´770+12´322
\ x = -5 and y= 12.
ii)
a=
11+7i and b= 3+7i in Z(i) where
Solution:
11+7i= (1-i)´(3+7i)+(1+3i)………..(1)
3+7i = (2-i)´(1+3i)+2i-2…………(2)
1+3i = (1-i)´(2i-2)+(i-1)………….(3)
2i-2 = 2´(i-1)+0
Hence g.c.d = d(11+7i,3+7i)
= i-1
And we know
For x and y
1+3i= (11+7i)- (1-i)´(3+7i) [
from(1)]
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image002.gif)
(2i-2)(1-i)=
(1+3i)-(i-1) [
from(3)]
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image002.gif)
Multiply (1) by 2-i
Then (11+7i)(2-i)= {(1-i)´(3+7i)+(1+3i)}(2-i)
Or, (11+7i)(2-i)= (1-i)(2-i)´(3+7i)+(1+3i)(2-i)
Or, (11+7i)(2-i)= (2-i-2i-1)(3+7i)+(1+3i)(2-i)
Or, (11+7i)(2-i)= (1-3i)(3+7i)+(1+3i)(2-i)
Or, (1+3i)(2-i)= (11+7i)(2-i)- (1-3i)(3+7i)………….(4)
Multiplying (2) by (1-i)
(3+7i)(1-i) = (2-i)(1-i)´(1+3i)+(2i-2)(1-i)
= (1-i)´(1+3i)(2-i)+ (1+3i)-(i-1)
(i-1) = (1-i){(11+7i)(2-i)-
(1-3i)(3+7i)}+ (11+7i)- (1-i)´(3+7i)-(1-i)(3+7i) [
from(1),(3)&(4)]
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image002.gif)
=[(1-i) (2-i)+1](11+7i)-[(1-i)(1-3i)+(1-i)+(1-i)] (3+7i)
= (2-i-2i-1+1) (11+7i) -[1-3i-i-3+2-2i] (3+7i)
= (2-3i) (11+7i)+6i (3+7i)
Hence x = 2-3i
Y = 6i
Solution:
Here
a=17, n= 27
Now 27= 1´17+10
17=
1´10+7
10=
1´7+3
7= 2´3+1
Now 10=27-1´17
7=
17-1´10
=
17-1´(27-1´17)
=
17-1´27+1´17
= 2´17-1´27
=
27-1´17-1´(
2´17-1´27)
=
27-1´17-2´17+1´27
= 2´27-3´17
1= 7-2´3
= 2´17-1´27-2´( 2´27-3´17)
= 2´17-1´27-4´27+6´17
= 8´17-5´27
1.
Compute the remainder when 350 is
divided by 37.
Solution:
We know
34 º 7mod37
38 º 12mod37
316º 33mod37
332º 16mod37
So 38.332 = 340º 7mod37
Again,
35º 21mod37
310º 34mod37
So 350=340.310º 16mod 37
Hence the
remainder is 16.
|
Rough part
34=81,
37)81(2
74
7
72=49, 37)49(1
37
12
122=144, 37)144(3
111
33
332=1089,
37)1089(29
74
349
333
16
|
12´16=192
37)192(5
185
7
35=243
37)243(6
222
21
212=441
37)441(11
37
71
37
34
Lastly 34´7=238
37)238(6
222
16
is the
ans.
|
2.
Does
the set of all matrices of the form G=
,
R under matrices multiplication form a group? Justify your answer.
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image010.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image012.gif)
Solution:
i)
Closure property
Let A=
and B=
for all
R
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image014.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image016.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image018.gif)
Now AB=
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image020.gif)
= ![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image022.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image022.gif)
= ![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image024.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image024.gif)
ii)
Associative
property
Let A=
,B=
and C=
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image014.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image016.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image026.gif)
Then A(BC)= ![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image028.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image028.gif)
= ![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image030.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image030.gif)
=
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image032.gif)
Again
(AB)C= ![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image034.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image034.gif)
= ![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image036.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image036.gif)
= ![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image038.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image038.gif)
Hence A(BC)= (AB)C
iii)
Exixtence of
identity
For all
and A=
there
exist
i.e I=
=
such that
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image040.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image014.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image042.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image044.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image046.gif)
AI=
A
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image048.gif)
iv)
Existence of
inverse
For all A=
there exist A-I=
=
=
=![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image056.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image014.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image050.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image052.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image054.gif)
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image056.gif)
Such that A.A-I=I
Hence it forms a group under matrix multiplication.
3.
Prove
that the set G=Q-{1} is a group under binary operation * defined by a*b =
a+b-ab for all a,b
G.
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image058.gif)
Solution:
i)
Closure law :
For all a,bÎG , a*b=a+b-abÎG
ii)
Associative
property
For all a,b,cÎG,
a*(b*c)=a*(b+c-bc)=a+(b+c-bc)-a(b+c-bc)=a+b+c-bc-ab-ac+abc
(a*b)*c= (a+b-ab)*c= (a+b-ab)+c-(a+b-ab).c= a+b-ab+c-ac-bc+abc
So a*(b*c)= (a*b)*c
iii)
Existence of
Identity
For all aÎG $ eÎG such that a*e=a
or, a+e-ae=a
or, e(1-a)=0
either e=0 or a=1 but a
1
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image060.gif)
so
e=0 ÎG.
iv)
Existence of
inverse
For all aÎG $ bÎG such that
a*b=e=0
a+b-ab=0
b(1-a)=-a
\b=
ÎG
![](file:///C:/Users/inter/AppData/Local/Temp/msohtmlclip1/01/clip_image062.gif)
Hence it forms a group under * operation.
No comments:
Post a Comment